Report of the Director General to the 2019 WIPO Assemblies - World Intellectual Property Organization (Geneva, Switzerland World Intellectual Property Organization, 2019)
This report is a presentation of the work accomplished by the Organization during the year that has passed since the last meeting of the WIPO Assemblies.
Keywords: INTELLECTUAL PROPERTY ORGANIZATION -- ASSEMBLIES